PENERAPAN METODE MODELING UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PUISI KELAS II SEKOLAH DASAR - Waliyo, Waliyo (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
Indonesian language learning is not optimal. This is due to less optimal learning, including: (1) learning methods and tools are less varied; (2) learning strategies are few; (3) do not provide opportunities to develop the competencies possessed by students; (4) the lack of encouragement of students in learning; (5) Lack of students' attention in reading; (6) Students do not participate actively in learning. The purpose of this research is to confirm reading skills through modeling procedures. The concept of this research is programming, implementation, monitoring, reflection. The research location was at SD Negeri 190/VIII Perintis, Tebo Regency, with 23 research subjects. The method of collecting information uses student monitoring sheets. The base is obtained from the results of observation tests and selection. The monitoring results which proved that changes in students' activities to be more active in learning to read poetry in cycle I obtained an average of 2.91 with a percentage of 73% and cycle II obtained an average of 3.18 with a percentage of 78%. The results of students' poetry reading skills in cycle I, in general, the score obtained by 67 whereas in cycle II generally increases to 76 with a KKM of 65, which means that they have fulfilled the specified KKM.